MUSICAL ELEMENTS OF THE RHYTHMIC ORGANIZATION OF THE DRAMATIC ACTION IN PLAYS «THE SONG OF ISRAEL» BY V. VYNNYCHENKO AND «SVICHKA’S WEDDING» BY I. KOCHERHA - Олексюк, Г. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article researches the role of musical elements in the rhythmic organization of the dramatic action of such plays by Volodymyr Vynnychenko and Ivan Kocherha as, respectively, «The Song of Israel» («Kol-Nidre») and «Svichka’s Wedding». It proves that such syncretism of literary and musical images helped develop a dramatic show, unfold a conflict, an inner and outer structure of the Ukrainian authors’ dramas in general. Simultaneously, it focuses attention on national playwrights’ employment of modern poetics, marked by actual for that time (the 20-30s of the XXth c.) syncretism of arts.